PENGARUH PEMBERIAN KREDIT DAN NON PERFORMING LOAN (NPL) TERHADAP PROFITABILITAS PADA BANK RAKYAT INDONESIA PERIODE 2006-2015 - Ramadhany, Citra; Putro, Tri Sukirno; Yovita, Indri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimes to analyze the effect inflicted by The variable, Credit Distribution and Non Performing Loan (NPL) towards the Profitability Bank Rakyat Indonesia Period 2006-2015. The research using quantitative analysis, partial and simultaneous analysis (multiple linear regression analysis using EVIEWS version 9.5 program facility). The results of tests that have been done, simultaneous regression test (F test) shows that the, Credit Distribution and Non Performing Loan (NPL) together significant influence toward the Bank Rakyat Indonesia. Test the partial regression (t test) indicates that the Credit Distribution variables have a significant influence toward the Bank Rakyat Indonesia, Non Performing Loan variables have a significant influence toward the Bank Rakyat Indonesia. The influence of the Bank Rakyat Indonesia described by a variable Credit Distribution and Non Performing Loan (NPL) jointly amounted to 77,8% (R2=0,778406) while the remaining 22,2% is influenced by other variables not examined in the study this research.Keyword: Credit Distribution, Non Performing Loan (NPL) and Profitability